PERANCANGAN USER INTERFACE EXPERIENCE (UIX) APLIKASI ANDROID SEBAGAI PENUNJANG SELF-DIRECTED LEARNING BAGI MAHASISWA - Fikri Cahya Muharram; Elin Rosalin (Narada : Jurnal Desain dan Seni, 2022)
Self-Directed Learning (SDL) is a student learning process in which students take responsibility for directing learning goals until these goals are met. The results of the questionnaire held by the researcher stated that there were several problems that students felt in the learning process with the SDL approach, including the absence of a facilitator to help students with learning difficulties; limited library references; a failure to identify the learning styles that stood out according to the student's personality; and the absence of a learning map that provides students with information. The goal of this research is to produce a prototype Android-based user interface experience (UIX) application that can aid student learning, which is classified as acceptable. Design thinking is used in this research to facilitate the development of UIX designs for future designs if necessary, namely empathize, define, ideate, prototype, and test. A UIX design test with system usability scale (SUS) metrics yields a score of 88.5, which is a grade A and acceptable for a prototype UIX design. In the test results, five participants completed several tasks and provided feedback for the proposed UIX design application, so that users can maximize their learning potential by using the Seltern Space application.